International practice of public legal education: a missing element in the justice system of Bangladesh - Yasmin, Taslima (© 2012 Commonwealth Secretariat., 2016)
This article was published in the Commonwealth Law Bulletin [© 2012 Commonwealth Secretariat.] and the definite version is available at : http://dx.doi.org/10.1080/03050718.2012.694998 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1080/03050718.2012.694998